The Other 94: Coming Growth Market for U.S. Farm Products - J. Don Looper (Journal of Applied Communications, 1984)
"The media have a vested interest in calamity." That remark, from a newsmagazine reporter in Washington, may help to explain why African drought is now in the news while chronic hunger affecting a half billion people may go virtually unreported for decades.